A Phenomenological Study:: A Pre-departure Study Abroad Course Interrupted by the COVID-19 Outbreak - Ward, James G.; Martin, Michael; Ward, Yaprak Dalat (Archives of Business Research, 2020)
The original plan of this research was to collect multiple sets of data from business students in a 2020 spring study abroad program including the pre-departure course, the experiential learning in Thailand and post experience. When the World Health Organization (2020c) categorized the COVID-19 outbreak a pandemic, the pre-departure course was interrupted, resulting in the remaining sections of the program to be cancelled. To date, since no previous research was available on a pre-departure course interrupted by a pandemic of this kind, the experiences of the two faculty members teaching the course became central to the research making this study phenomenological. The experiences were captured by daily notes with reflections leading to four key findings: 1. The course lacked skills training and needed to be redesigned as it would be offered in spring 2021. Adding practical applications to the comprehensive collection of materials would lead students to start shifting their mindsets prior to the trip rather than during the trip resulting in maximized experiences. 2. The COVID-19 outbreak was unprecedented in that it was not a short-lived occurrence but an on-going crisis. The uniqueness of the situation brought futuristic thinking and scenario planning to the forefront when developing and implementing such global programs. 3. Faculty were not prepared for an on-going crisis. To be able to cope with similar uncertainties and act decisively, faculty leading such experiences needed training in futuristic thinking and scenario planning. 4. Faculty country-expertise strengthened student trust when teaching the course. Developing, teaching such courses, and leading such experiences need to be backed up by location-expertise to foster confidence for optimal benefits.